Bond Stress-Slip Models and Behavior of Aluminum Alloys-Concrete Interface - Mirghani, Ahmed (2017)
A Master of Science thesis in Civil Engineering by Ahmed Mirghani entitled, "Bond Stress-Slip Models and Behavior of Aluminum Alloys-Concrete Interface," submitted in January 2017. Thesis advisor is Dr. Jamal Abdalla and thesis co-advisor is Dr. Rami Hawileh. Soft and hard copy available.